2006
DOI: 10.1203/01.pdr.0000203550.50258.5a
|View full text |Cite
|
Sign up to set email alerts
|

Adult Bone Marrow-Derived Stem Cells for the Lung: Implications for Pediatric Lung Diseases

Abstract: Bronchopulmonary dysplasia (BPD) and cystic fibrosis (CF) are two common serious chronic respiratory disorders without specific treatments affecting children. BPD is characterized by an arrest in alveolar growth in premature infants requiring respiratory support. CF is the most common fatal inherited genetic disorder characterized by abnormally thick mucus secretions, recurrent infection and ultimately lung destruction. One commonality between these two diseases is the promise of utilizing stem cells therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 52 publications
0
13
0
1
Order By: Relevance
“…ES cells are pluripotent cells and are derived from the inner cell mass of the blastocyst stage of embryos (30). They are able to form any cell type and tissue in the animal body and therefore have great therapeutic capacity to regenerate any damaged tissue (23). ES cells isolated from the inner cell mass of a blastocyst can be characterized in vivo by the formation of chimeric embryos when injected into an immunocompromised host, and by differentiation in vitro to form embryoid bodies (31).…”
Section: Stem Cells Definition and Backgroundmentioning
confidence: 99%
“…ES cells are pluripotent cells and are derived from the inner cell mass of the blastocyst stage of embryos (30). They are able to form any cell type and tissue in the animal body and therefore have great therapeutic capacity to regenerate any damaged tissue (23). ES cells isolated from the inner cell mass of a blastocyst can be characterized in vivo by the formation of chimeric embryos when injected into an immunocompromised host, and by differentiation in vitro to form embryoid bodies (31).…”
Section: Stem Cells Definition and Backgroundmentioning
confidence: 99%
“…Arrest of such tissue maturation process may induce conditions like bronchopulmonary dysplasia (BPD) [4], which is characterized by the arrest in alveolar growth in premature infants, causing neonatal respiratory distress syndrome. Recently it had been suggested that the involvement of such cells potentially play important roles in the recovery process of certain diseases such severe acute respiratory syndrome (SARS).…”
Section: The Roles Of Stem/progenitor Cells In Lung Growth and Repairmentioning
confidence: 99%
“…The goal of stem cell therapy is to therapeutically deliver to the damaged organs stem/progenitor cells to augment the regenerative capacity of the damaged tissue, thus preserving its function. The experimental pulmonary disease models which have been studied to date include acute respiratory distress syndrome [6,13], chronic lung diseases of pre-maturity [4], compensatory pulmonary hyperplasia following lung resections [14], bronchiolitis obliterans [3], cystic fibrosis [15,16], emphysema [17][18][19][20], idiopathic pulmonary hypertension [21][22][23][24][25] and pulmonary fibrosis [26]. The majority of these studies are very preliminary and far premature from clinical trials and therapeutic use.…”
Section: Regenerative Therapy By Stem/prog-enitor Cell Transplantationmentioning
confidence: 99%
“…Additional evidence for lung engraftment following bone marrow or lung transplantation comes from biopsies of human lung [16][17][18][19]. Other aspects of adult stem cell biology in lung disease have been thoroughly reviewed recently [20,21].…”
Section: Introductionmentioning
confidence: 99%